2004
DOI: 10.1021/om049716j
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Rich, Bulky Ruthenium PNP-Type Complexes. Acceptorless Catalytic Alcohol Dehydrogenation

Abstract: Reaction of the electron-rich, bulky tridentate PNP ligand (2,6-bis-(di-tert-butylphosphinomethyl)pyridine) with Ru(PPh3)3Cl2 at 65 °C resulted in formation of a solution containing the dinitrogen monomeric Ru(II) complex 1a and the N2-bridged dinuclear Ru(II) complex 1b, which can be interconverted. Passing argon through the solution results in formation of pure 1b. The Ru(II) hydride dinitrogen complex 2 was obtained by the reaction of complex 1b with 2 equiv of NaBEt3H. Complex 1b reacted with 4 equiv of Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
144
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(153 citation statements)
references
References 41 publications
5
144
0
4
Order By: Relevance
“…[51] At that time, no clear mention was made of the possible involvement of a complex that featured the dearomatized structure of the ligand backbone 12 during catalysis. The molecular structure for a Ru complex with the dearomatized analogue of 12 iPr was determined recently.…”
Section: Cooperative Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[51] At that time, no clear mention was made of the possible involvement of a complex that featured the dearomatized structure of the ligand backbone 12 during catalysis. The molecular structure for a Ru complex with the dearomatized analogue of 12 iPr was determined recently.…”
Section: Cooperative Catalysismentioning
confidence: 99%
“…[55] Gibson et al independently reported the formation of some Ru complexes with 12 tBu in 2004 (Scheme 13), [62] simultaneously with the first application of this catalyst system for the acceptorless dehydrogenation of alcohols by Milstein and co-workers. [51] In the former report, a RuÀOH species that arose from facile deprotonation of an elusive intermediate aquo complex was also discussed, as well as some other interesting compounds. No mention was made of the potential involvement of the PNP backbone during these reactions.…”
Section: Other Chemistry With Rutheniummentioning
confidence: 99%
“…The decision on which substituent is appropriate is not addressed in this study. 2) Mononuclear ruthenium complexes, such as 1 [16] and 2, [17] with an ether and a nitrogen donor group, respectively, in the ligand backbone and each bonding one N 2 molecule end-on, had already been shown to be available synthetically and were characterized crystallographically, thus proving that N 2 complexes of this kind are accessible. For 1 it was also shown that N 2 can be displaced by H 2 , indicating that dissociation or reassociation of either H 2 or N 2 should be possible under appropriate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[51] Zu dieser Zeit wurde nicht klar formuliert, dass eine Form des Komplexes an der Katalyse beteiligt sein könnte, in der das Ligandgerüst 12 in desaromatisierter Form vorliegt. Die Molekülstruktur eines Rutheniumkomplexes mit dem Liganden 12 iPr in desaromatisierter Form wurde kürzlich bestimmt.…”
Section: Kooperative Katalyseunclassified